An All‐Solution‐Based Hybrid CMOS‐Like Quantum Dot/Carbon Nanotube Inverter. Issue 35 (17th July 2017) - Shulga, Artem G.; Derenskyi, Vladimir; Salazar‐Rios, Jorge Mario; Dirin, Dmitry N.; Fritsch, Martin; Kovalenko, Maksym V.; Scherf, Ullrich; Loi, Maria A.
Abstract : The development of low‐cost, flexible electronic devices is subordinated to the advancement in solution‐based and low‐temperature‐processable semiconducting materials, such as colloidal quantum dots (QDs) and single‐walled carbon nanotubes (SWCNTs). Here, excellent compatibility of QDs and SWCNTs as a complementary pair of semiconducting materials for fabrication of high‐performance complementary metal‐oxide‐semiconductor (CMOS)‐like inverters is demonstrated. The n‐type field effect transistors (FETs) based on I − capped PbS QDs ( V th = 0.2 V, on/off = 10 5, S S‐th = 114 mV dec −1, µ e = 0.22 cm 2 V −1 s −1 ) and the p‐type FETs with tailored parameters based on low‐density random network of SWCNTs ( V th = −0.2 V, on/off > 10 5, S S‐th = 63 mV dec −1, µ h = 0.04 cm 2 V −1 s −1 ) are integrated on the same substrate in order to obtain high‐performance hybrid inverters. The inverters operate in the sub‐1 V range (0.9 V) and have high gain (76 V/V), large maximum‐equal‐criteria noise margins (80%), and peak power consumption of 3 nW, in combination with low hysteresis (10 mV). Abstract : An all‐solution‐processable hybrid CMOS‐like inverter based on PbS quantum dots (n‐type) and single‐walled carbon nanotubes (p‐type) is demonstrated. The inverter operates in the sub‐1 V range (0.9 V) and has high gain (76 V/V), large noise margins (80%), low hysteresis (10 mV), and low peak power consumption (3 nW).